Cervical cancer apparent diffusion coefficient values during external beam radiotherapy. (January 2019) - de Boer, Peter; Mandija, Stefano; Werensteijn-Honingh, Anita M.; van den Berg, Cornelis A.T.; de Leeuw, Astrid A.C.; Jürgenliemk-Schulz, Ina M.
Abstract: Background and purpose: Apparent diffusion coefficient (ADC) reflects micro-enviromental changes and therefore might be useful in predicting recurrence prior to brachytherapy. The purpose of this study is to evaluate change in ADC of the primary tumour and pathologic lymph nodes during treatment and to correlate this with clinical outcome. Material and methods: Twenty patients were included who received chemoradiation for locally advanced cervical cancer between July 2016 and November 2017. All patients underwent magnetic resonance imaging (MRI) prior to treatment, and three MRIs in weeks 1/2, 3 and 4 of treatment, including T2 and diffusion weighted imaging ( b- values 0, 200, 800 s/mm 2 ) for determining an ADC-map. Primary tumour was delineated on T2 and ADC-map and pathologic lymph nodes were delineated only on ADC-map. Results: At time of analysis median follow-up was 15 (range 7–22) months. From MRI one to four, primary tumour on ADC-map showed a significant signal increase of 0.94 (range 0.74–1.46) × 10 −3 mm 2 /s to 1.13 (0.98–1.49) × 10 −3 mm 2 /s (p < 0.001). When tumour was delineated on T2, ADC-value signal increase (in tumour according to T2) was similar. All 46 delineated pathologic lymph nodes showed an ADC-value increase on average from 0.79 (range 0.33–1.12) × 10 −3 mm 2 /s to 1.14 (0.59–1.75) × 10 −3 mm 2 /s (p < 0.001). The mean tumour/suspected lymph node volumes decreased respectively 51/40%. Four patients developed relapse (one local and three nodal), without clear relation with ΔADC. However, the median volume decrease of the primary tumour was substantially lower in the failing patients compared to the group without relapse (19 vs. 57%). Conclusions: ADC values can be acquired using T2-based tumour delineations unless there are substantial shifts between ADC-mapping and T2 acquisition. It remains plausible that ΔADC is a predictor for response to EBRT. However, the correlation in this study was not statistically significant.